ALIH KODE DAN CAMPUR KODE DALAM INTERAKSI SEHARI-HARI OLEH SANTRIWATI PONDOK MODERN DARUL FALACH TEMANGGUNG (KAJIAN SOSIOLINGUISTIK) (Lisanul Arab: Journal of Arabic Learning and Teaching, 2023)
Santriwati Tahfidzul Qur'an Pondok Modern Darul Falach Temanggung is a modern hut that applies the use of three languages. Thus, santriwati uses three languages in their daily lives, namely Arabic, English and Indonesian. This is what triggers the occurrence of code switching and code mixing events in interactions in which it is indicated that there is a change in the meaning of the Arabic language. This study aims to describe the form of code switching and code mixing as well as the factors causing code switching and code mixing itself. This research is a qualitative research with ethnographic design. The data in this study is the daily speech of santriwati tahfidzul qur'an. the instrument in this study is in the form of a data card. The data collection technique in this study used the listening method and the interview method. Data analysis techniques in this study used the descriptive method of quality. The results of this study showed that the language used in communication by Tahfidzul Quran santriwati Pondok Modern Darul Falach Temanggung found 113 data with the following details; 27 data in the form of code transfer, 75 data in the form of code mixes and 11 data indicated changes in the meaning of Arabic in Indonesian, Javanese and English. From this data, code mix data is the most data than code transfer data and meaning changes, and for the least data is meaning change data.